The incorporation of girls of 9 to 10 years to the soccer practice - Frank Guerra-Reyna (Universidad de Guantánamo, 2014)
The incorporation of girls to the practice of soccer is regarded in this paper as a first step for the development of this sport, in preparation for a socially useful life, product of the physical and moral formation. We set from the activities, actions and games as physical, instructive, recreational and motivational tools making the psycho- pedagogic work easy, sustained in the alternative models of teaching and incorporating the precisions, the indications and the methods appropriate for the fulfillment of these objectives, which constitute the contribution of this investigation. Finally it could be verified that the level of approval of the system of activities proposed is high, evidenced in the conclusive result obtained after the assessment and the consultation to experts when evaluating the stages and categories of very adequate.